Recent Developments in Deciphering the Biological Role of Plant Complex N-Glycans - Strasser, Richard (Frontiers in Plant Science, 2022)
Asparagine (N)-linked protein glycosylation is a ubiquitous co- and posttranslational modification which has a huge impact on the biogenesis and function of proteins and consequently on the development, growth, and physiology of organisms. In mammals, N-glycan processing carried out by Golgi-resident glycosidases and glycosyltransferases creates a number of structurally diverse N-glycans with specific roles in many different biological processes. In plants, complex N-glycan modifications like the attachment of β1,2-xylose, core α1,3-fucose, or the Lewis A-type structures are evolutionary highly conserved, but their biological function is poorly known. Here, I highlight recent developments that contribute to a better understanding of these conserved glycoprotein modifications and discuss future directions to move the field forward.